Relation between emotional intelligence and psychological well-being - Ong, Cheng Hong. (2011)
This exploratory study investigates the relation between emotional intelligence and three aspects of psychological well-being for a group of Secondary Three adolescents from a neighbourhood school. The three aspects of psychological wellbeing examined were namely: satisfaction with life, positive affect and negative affect. The Trait Meta-Mood Scale was used as a measure of emotional intelligence. The Satisfaction With Life Scale, and the Positive and Negative Affect Schedule were measures for psychological well-being.